Optimal immediate sagittal alignment for kyphosis in ankylosing spondylitis following corrective osteotomy - Luo, Jianzhou; Yang, Kai; Yang, Zili; Feng, Chaoshuai; Li, Xian; Luo, Zhenjuan; Tao, Huiren; Duan, Chunguang; Wu, Tailin (Frontiers in Surgery, 2022)
Purpose: To investigate the optimal immediate sagittal alignment of kyphosis in ankylosing spondylitis (AS) following corrective osteotomy. Methods: Seventy-seven AS patients who underwent osteotomy were enrolled. Radiographic parameters, including global kyphosis (GK), lumbar lordosis (LL), T1 spinopelvic inclination (T1SPI), sagittal vertical axis (SVA), T1 pelvic angle (TPA), pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), and PI and LL mismatch (PI-LL), were collected. The clinical outcome was evaluated using the Scoliosis Research Society-22 questionnaire (SRS-22) and Oswestry Disability Index (ODI). At the final follow-up, SVA> 5 cm was regarded as sagittal imbalance, and a total ODI ≤ 20 or total SRS-22 score ≥ 4 was considered to indicate a good clinical outcome. Results: Seventy-seven patients with an average age of 37.4 ±8.6 years were followed up for 29.4±4.2 months. At the final follow-up, GK, LL, PT, SS, TPA and T1SPI showed some degree of correction loss (P<0.05). The follow-up parameters could be predicted with the immediate postoperative parameters through their linear regression equation (P<0.05). The postoperative immediate T1SPI, TPA, SVA and PI were also highly correlated with the clinical outcome (ODI and/or SRS-22) at the final follow-up (P<0.05). Based on the relationship, the optimal immediate sagittal alignment for obtaining good clinical outcome was determined: T1SPI≤0.9°, TPA≤31.5° and SVA≤9.3 cm. AS patients with PI≤49.2° were more likely to achieve the optimal alignment and obtained lower ODI and a lower incidence of sagittal imbalance than those with PI>49.2° at the final follow-up (P<0.05). Conclusion: Postoperative immediate parameters could be used to predict the final follow-up parameters and clinical outcome. The optimal postoperative immediate sagittal alignment of AS patients was T1SPI≤0.9°, TPA≤31.5° and SVA≤9.3 cm, providing a reference for kyphosis correction and a means for clinical outcome evaluation. Patients with a lower PI (≤49.2°) were more likely to achieve optimal alignment and obtain satisfactory clinical outcomes.